Community Behavior about the Utilization of Family Latrines in the Work Area of Panei Tongah Puskesmas, Panei District, Simalungun Regency - Jumadiah Wardati (Institute of Computer Science (IOCS), 2022)
One of the targets of health development is to increase healthy living behavior and a healthy environment. This study aims to obtain a description of community behavior which includes community knowledge, attitudes and actions regarding the use of family latrines in the Panei Tongah Health Center Work Area, Panei District, Simalungun Regency which has been carried out in July - September 2020. The type of research is a descriptive survey research with an observational approach. The population in this study included all families in the Panei Tongah Health Center working area, Panei District, amounting to 6939 families and spread over 17 sub-districts/villages, namely Panei Tongah Village, Bah Bolon Tongah Village, Simpang Raya Dasma Village, Simpang Raya Village, Mekar Sari Raya Village, Sipoldas Village, Bangun Dasmariah Village, Bangun Rakyat Village, Bangun Sitolubah Village, Simantin Pane Dame Village, Sigodang Village, West Sigodang Village, Rawang Pardomuan Nauli Village, Janggir Leto Village, Siborna Village, NauliBaru Village, Bahliran Siborna Village. So the number of samples in this study was 378 families. Sampling was done randomly. Respondents' actions regarding the use of family latrines 68.5% had positive actions while 31.5% had negative actions. Respondents who used family latrines were only 44.7% and 55.3% did not. Respondents who use family latrines are 37.3% while those who do not use latrines are 62.7%. So that intensive counseling and guidance is needed that is adjusted to the level of knowledge possessed by respondents, both in groups and individually in order to increase efforts to implement appropriate community attitudes and actions regarding the use of family latrines.